1989
DOI: 10.1128/aem.55.3.684-688.1989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of increased aspartate availability on lysine formation by a recombinant strain of Corynebacterium glutamicum and utilization of fumarate

Abstract: Aspartate availability was increased in Corynebacterium glutamicum strains to assess its influence on lysine production. Upon addition of fumarate to a strain with a feedback-resistant aspartate kinase, the lysine yield increased from 20 to 30 mM. This increase was accompanied by the excretion of malate and succinate. In this strain, fumaric acid was converted to aspartate by fumarate hydratase, malate dehydrogenase, and aspartate amino transferase activity. To achieve the direct conversion of fumarate to aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…[257,267,273]). Menkel et al [284] already showed that addition of fumarate to the growth medium and thus increasing the oxaloacetate and aspartate availability led to an about 30% higher lysine yield with a producer strain. From this result it was concluded that the supply of the precursors oxaloacetate or aspartate is rate limiting for optimal lysine production.…”
Section: Metabolic Engineering Of the Node For Amino Acid Productionmentioning
confidence: 99%
“…[257,267,273]). Menkel et al [284] already showed that addition of fumarate to the growth medium and thus increasing the oxaloacetate and aspartate availability led to an about 30% higher lysine yield with a producer strain. From this result it was concluded that the supply of the precursors oxaloacetate or aspartate is rate limiting for optimal lysine production.…”
Section: Metabolic Engineering Of the Node For Amino Acid Productionmentioning
confidence: 99%
“…The wild type of Corynebacterium glutamicum (ATCC 13032), its two lysine-producing mutants MH 20-22B [8] and DG 52-5 [9] and AS72 (derived from DG 52-5 lacking diaminopimelate dehydrogenase (Ddh-) [2] were used. They were inoculated into 100 ml brain-heart infusion (Difco, Detroit, USA) as a preculture medium.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…Another prerequisite is the determination of I3C enrichments in the carbon atoms of either aspartate or pymvate. Since these intermediates are only found in limited amounts in culture fluids [9], we undertook label determination in alanine derived directly from pyruvate. In a culture of strain DG 52-5, 12 mM alanine was found, with 3.0% 13C enrichment at C-2 and 24.6% at C-3 determined.…”
Section: Assessment Of the Validity Of The Flux Distribution Modelmentioning
confidence: 99%
“…1a) and introduced into C. glutamicum ATCC 13032 by electroporation. Cells in which integration had occurred by a single cross-over cell were isolated by selection for kanamycin resistance (Km R ) on CGIII agar (Menkel et al, 1989), and confirmed by PCR with two primer pairs, one specific for integration upstream of the gene of interest (PKTHYX1 and PKTHYX2), and the other specific for integration downstream (THYXPK1 and THYXPK2). Single cross-over cells were grown on LB agar plates containing 10% w/v sucrose to resolve the suicide plasmid, in the absence of NaCl and kanamycin.…”
Section: Deletion Mutagenesis and Complementation Of C Glutamicum Thyxmentioning
confidence: 99%